E-102 Use of pipeline embolization device for ICA reconstruction through false lumen. (22nd July 2018) - de Macedo Rodrigues, K; Kuhn, A; Rex, D; Massari, F; Puri, A; Wakhloo, A
Abstract : Purpose: To demonstrate a novel use of the pipeline embolization device (PED) for reconstruction of a dissected cervical internal carotid artery (ICA) bridging the true arterial lumen through its false lumen. Case report: 50-year-old male with daily right periorbital and frontal headaches with associated rhinorrhea, lacrimation and right eye ptosis for 3 months started 2 days after motor vehicle collision. Neurological exam was otherwise unremarkable. He was initially diagnosed as having cluster headaches. Imaging findings: To exclude organic causes of headache, an MRI and MR angiogram of the brain were obtained and a cervical right ICA dissection was partially visualized. CT angiogram demonstrated a dissection of the cervical right ICA at the level of a vessel kinking with associated pseudoaneurysm compressing the true arterial lumen which appeared severely stenotic. Patient was then started on dual antiplatelet regimen. DSA confirmed CTA findings and showed insufficient collateral flow to the right ICA territory on balloon test occlusion. Given the vessel loop, probability of successful navigation of a carotid artery stent or balloon mounted coronary stent was deemed low considering its characteristic stiff construct. Decision was made to utilize a PED given flexibility, diameter compatibility and better conformation to vessel curvature. Gentle angioplasty was performed at the entry and reentry point prior to and after stent deployment. Two partially overlapped PED and one Precise Pro RX carotid stent were used to bridge the proximal and distal healthy lumen through the false lumen. Headaches resolved after endovascular treatment. Follow-up angiogram performed at 7 month showed complete occlusion of the excluded lumen with excellent flow through the stent construct. Summary: Successful and uncomplicated reconstruction of a dissected cervical ICA demonstrated with the use of a PED bridging the proximal and distal true lumen via false lumen. Disclosures: K. de Macedo Rodrigues: None. A. Kuhn: None. D. Rex: None. F. Massari: None. A. Puri: 1; C; Stryker Neurovascular, Covidien. 2; C; Codman Neurovascular, Covidien. 4; C; InNeuroCo. A. Wakhloo: 1; C; Philips Healthcare. 2; C; Stryker Neurovascular. 3; C; Harvard Postgraduate Course, Miami Cardiovascular Institute. 4; C; InNeuroCo.